2003
DOI: 10.1097/01.asn.0000037403.95126.03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Renal Failure on Cardiac Contractile Function, Calcium Cycling, and Gene Expression of Proteins Important for Calcium Homeostasis in the Rat

Abstract: Abstract. Patients with chronic renal failure frequently develop cardiac hypertrophy and diastolic dysfunction; however, the mechanisms by which this occurs are still unclear. Male Sprague-Dawley rats were subjected to 5/6 nephrectomy and studied for their isolated myocyte function, calcium cycling, and gene expression of proteins important in calcium homeostasis after 4 wk. Comparable rats subjected to suprarenal aortic banding for the same duration were used for comparison. Rats subjected to 5/6 nephrectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
66
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 55 publications
7
66
1
Order By: Relevance
“…However, the mechanism which this occurs and the major players in the pathogenesis are still unclear. Our study demonstrated that treatments of arterial hypertension and anemia partially ameliorated but did not completely correct cardiac and left ventricular hypertrophy in uremic rats, which was in an agreement with the results presented by others (Rambausek et al, 1985;Kennedy et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the mechanism which this occurs and the major players in the pathogenesis are still unclear. Our study demonstrated that treatments of arterial hypertension and anemia partially ameliorated but did not completely correct cardiac and left ventricular hypertrophy in uremic rats, which was in an agreement with the results presented by others (Rambausek et al, 1985;Kennedy et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Fast-migrating V1 isomyosin was increased in uremia. In end-stage-renal disease the elevated serum hepatocyte growth factor (Malatino et al, 2003) or calcium homeostasis (Kennedy et al, 2003) seemed to be associated with LVH. However, the mechanism which this occurs and the major players in the pathogenesis are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we have previously used Indo-1 to study calcium transients with our system. 28,33,53 However, in these experiments in which we anticipated substantial increases in the pHi in the aldosteronetreated cells, we chose to use Fluo-3 because it is relatively pH-insensitive while still giving extremely high signal-tonoise ratio. Despite our stable time controls, it is possible that during the short-term experiments performed, some dye leakage occurred in the spironolactone group, and some increases in cytosolic calcium, especially systolic values, could have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…Uremia is associated with depressed cardiac function at the level of the myocyte, [123][124][125] independent of gross alterations in cardiac structure, or ␤-adrenoreceptor desensitization. 123,124 Although the underlying mechanism is not fully understood, two groups independently identified prolongation of the calcium transient, 123,125 without a change in amplitude or rate of sarcoplasmic reticulum calcium release.…”
Section: Calcium Cyclingmentioning
confidence: 99%